Analysis of Factors Determinant of Stunting in Children Ages 2-5 Years in the Working Area of Pustu Kedunglengkong at Dlanggu Public Health Center Mojokerto - Rita Sugihati; Nurwijayanti Nurwijayanti; Indasah Indasah (Journal for Quality in Public Health, 2020)
Nutritional problems are still a trend at the moment is the problem of stunting (short). Stunting (short) in Indonesia is a problem that is often overlooked because it is considered not to affect their children's future. Most of the community does not dispute the slow growth of the child's height when a toddler. While the child is still healthy and frisky, stunting (short) is not a problem that needs to be addressed. Design research is crossectional approach analytic. The research of the variable intake of food, infection, disease history of availability of food, nutrition and parenting as the independent variable and the dependent variable as a stunting Incident. Population research namely the entire toddler at toddler 397 Pustu Kedunglengkong as much as 2-5 years of age. Samples taken by random sampling technique as much as 101 respondents. Data collected by questionnaire instrument and processed by using coding, editing, tabulating and scoring as well as tested with logistic regression test. The results of this research show that partially or alone – its own independent variable may affect the occurrence of the dependent variables because the value significance < 0.05. Independent variable affect simultaneously or together can affect the incidence of stunting, indicated by the value of the overall percentage of 78 meaning independent variable can affect both variables of 78%. The results of this research show the value of the most high is wald of infectious diseases. So it can be declared of infectious diseases is the dominant factor affecting the occurrence of stunting. Because the children often experience the infectious disease then it will decrease the frequency of child food and nutrients are not absorbed optimally so that it can menggangun the growth of the child